Percutaneous insertion of peritoneal dialysis catheters by the nephrologist (modified Seldinger technique) - Karlien Francois; Dieter De Clerck; Tom Robberechts; Freya Van Hulle; Stefan Van Cauwelaert; Ine Luyten; Daniel Jacobs-Tull (RDPLF, 2021)
A proper functioning access to the peritoneal cavity is the first and foremost requirement to start peritoneal dialysis. Most commonly, peritoneal dialysis catheters are inserted using a surgical approach. Laparoscopic peritoneal dialysis catheter insertion is the recommended surgical technique because it offers to employ advanced adjunctive procedures that minimize the risk of mechanical complications. In patients with low risk of mechanical catheter complications, such as patients without prior history of abdominal surgery or peritonitis, and in patients ineligible for general anesthesia, the percutaneous approach of peritoneal dialysis catheter insertion is an alternative to surgical catheter insertion. Percutaneous insertion of peritoneal dialysis catheters can be performed by a dedicated nephrologist, interventional radiologist, surgeon or nurse practitioner under local anesthesia, either with or without image guidance using ultrasound or fluoroscopy. Several reports show similar catheter function rates, mechanical and infectious complications and catheter survival for percutaneously inserted peritoneal dialysis catheters compared to surgically inserted peritoneal dialysis catheters. This article describes the percutaneous insertion of peritoneal dialysis catheters technique adopted at Universitair Ziekenhuis Brussel since 2015. Our technique is a simple low-tech modified Seldinger procedure performed by the nephrologist and not using fluoroscopy guidance. We describe the excellent outcomes of our percutaneously inserted peritoneal dialysis catheters and offer a practical guide to set up your own percutaneous catheter insertion program.